ANÁLISIS DE LA FIGURA JURÍDICA DE VIOLENCIA ESCOLAR Y SU INCORPORACIÓN EN LA LEY PARA PREVENIR Y ERRADICAR LA VIOLENCIA CONTRA LAS MUJERES - PINZON MOLINA, JOSE ANTONIO (2024)
An analysis of the legal framework governing school violence and its incorporation in the Law to Prevent and Eradicate Violence Against Women is provided in the following work, which reflects the latent problem present in educational institutions where students are violated by these legal figures in ways that are fundamental to their integral development as students. There has been a significant increase in the number of victims of school violence in the past few years as this problem has existed for quite some time in basic education and high school educational institutions. About 800 children and adolescents attempted suicide between the years 2021 and 2022 as a result of violence they are experiencing from peers or teachers in institutions. In order to protect and ensure the healthy development of children, this type of violence must be addressed. An objective of this study is to describe this behavior under the law and to suggest ways in which school violence may be controlled. In educational institutions, an environment of violence, good education, and a safe and healthy environment should be provided to guarantee that all members are able to effectively exercise all their rights in an environment free of violence, as well as an environment that provides a good environment for learning. Several methods were used to conduct this research in order to develop the current investigation, including legal, scientific, inductive, and deductive ones. As well, surveys and interviews were conducted with lawyers and directors of educational institutions in order to establish clear and pertinent criteria for verifying objectives, thus contributing to the achievement of these objectives., also allowed to reach conclusions, recommendations and reform proposals.